Organic synthesis via examination of selected natural products (World Scienetific, 2011)
Suitable for advanced graduate and undergraduate students, this book intends to expose them to a variety of strategies for the synthesis of organic compounds. It presents multiple approaches to each group of synthesis targets, and compares the approaches with one another with an eye on similarities and differences